Meningkatkan Hasil Belajar Siswa Pada Pembelajaran Matematika Materi Kubus Dan Balok Melalui Penerapan Model Pembelajaran PBL (Problem Based Learning) - Moh Nasrul Fuad (STAI Hidayatut Thullab Kediri, 2025)
This research is motivated by the low student learning outcomes in mathematics, particularly in the topics of cubes and cuboids, which require spatial visualization skills. The primary factor contributing to these low outcomes is the use of conventional teacher-centered learning models, which lead students to memorize formulas without understanding the underlying concepts. This study aims to improve student learning outcomes through the application of the Problem Based Learning (PBL) model. The research method employed is Classroom Action Research (CAR), conducted in two cycles consisting of planning, implementation, observation, and reflection. The subjects of this study were 33 students from class IX A at MTs Sunan Kalojogo. Data were collected using observation sheets, interviews, field notes, and written tests. The results indicated that the implementation of the PBL model significantly improved student learning outcomes. In Cycle I, the average score was 74.6 with a 73% completeness rate. Following improvements in Cycle II, the average score rose to 80.7 with a completeness rate of 94%. Thus, this study concludes that the PBL model is effective in enhancing student mastery and learning outcomes in the topics of cubes and cuboids